Young Blood Rescues the Cognition of Alzheimer's Model Mice by Restoring the Hippocampal Cholinergic Circuit. (1st October 2019) - Xia, Endi; Xu, Fengyan; Hu, Changbin; Kumal, Jay Prakash Prasad; Tang, Xudong; Mao, Dongsheng; Li, Yixuan; Wu, Di; Zhang, Rui; Wu, Shuliang; Sun, Liang
Abstract: An increasing number of studies have demonstrated the benefits of young individual-derived blood for aging-related diseases. However, the effects of young blood on the cognitive and cholinergic transmission defects in aging-associated Alzheimer's disease (AD) remain elusive. In the current study, we showed that young blood serum delivered intravenously attenuated deficits in hippocampal-dependent learning and memory, alleviated hippocampal Aβ plaque pathology, restored synapse formation and synaptic plasticity, repaired the hippocampal cholinergic circuit, and triggered several canonical neuroprotective mechanisms [including repressor element 1-silencing transcription factor (REST)/Forkhead box protein O1 (FOXO1) signaling] in aged AD model mice. However, pharmacological blockage of hippocampal cholinergic activity nearly abrogated the neuroprotective actions of young blood serum in AD mice. Thus, our findings suggest that exogenous young blood serum exerts therapeutic effects on AD-associated cognitive disorders and pathology by promoting hippocampal cholinergic input and simultaneously activating other neuroprotective mechanisms. Highlights: Young blood serum treatment ameliorated hippocampal-dependent cognitive disorder in AD model mice. Young blood serum treatment repressed Aβ pathology, restored synaptogenesis and synaptic plasticity in AD model mice. The therapeutic effects of young blood serum in AD were mediated partially by renewing hippocampal cholinergic input. The therapeutic effects were associated with canonical neuroprotective mechanisms including REST/FOXO1 signaling.